2022
DOI: 10.1002/hsr2.652
|View full text |Cite
|
Sign up to set email alerts
|

Pericardial effusion among children: Retrospective analysis of the etiology and short‐term outcome in a referral center in the south of Iran

Abstract: Background and Aims: We reinvestigated the causes, symptoms, and management of childhood pericardial effusion (PE) and its gradual changes during recent years in a referral pediatric cardiology center in the south of Iran. Methods:We retrospectively analyzed the profile of PE patients who were under 18 years old from 2015 to 2020. The patient's demographic, clinical, and paraclinical information was extracted and analyzed using SPSS software.Result: In general, 150 out of 63,736 admitted patients (0.23% of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
3
2
0
1
Order By: Relevance
“…PE or pericardial tamponade contributed to less than 1% of pediatric emergency admissions in our study. This is in agreement with reports from other countries [ 10 , 20 ]. This underscores the rarity of PE or pericardial tamponade in children.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…PE or pericardial tamponade contributed to less than 1% of pediatric emergency admissions in our study. This is in agreement with reports from other countries [ 10 , 20 ]. This underscores the rarity of PE or pericardial tamponade in children.…”
Section: Discussionsupporting
confidence: 94%
“…In this study, cough or shortness of breath was the most common PE presentation followed by fever or fast breathing. This is in line with other studies [ 4 , 8 , 15 , 20 22 ]. The median duration of illness of PE subjects was about two weeks in this study.…”
Section: Discussionsupporting
confidence: 94%
“…Regarding the etiology of pericardial effusion we observed that the most common etiological factor was para-pneumonic effusion which was found in 6 patients out of 18 (33.3%), while renal failure was found in 5 patients out of 18 (27.7%), malignancy was found in 4 patients (22.2%) while other factors were found only in 3 patients (16.6%), a study reported that renal failure was the leading cause of pericardial effusion while para-pneumonic effusion was second leading cause in their study. 20…”
Section: Discussionmentioning
confidence: 99%
“…Kondisi yang dialami pasien mungkin dapat menunjukkan keterkaitan antara satu dengan yang lain sesuai dengan patofisiologi dari penyakit. Efusi perikard merupakan suatu kondisi adanya akumulasi cairan antara 2 lapisan perikard (Mehdizadegan et al, 2022). Akumulasi cairan ini pada anak-anak memiliki etiologi yang bervariasi, bahkan pada studi Moreno, et al 2020 menyebutkan adanya perbedaan etiologi efusi perikard pada negara maju dan berkembang.…”
Section: Diskusi Kasusunclassified